Peran Bimbingan Perkawinan Pranikah dalam Mencegah Pernikahan Dini: Studi Kasus Kantor Urusan Agama (KUA) Kecamatan Puring Kabupaten Kebumen - Arini Nur Akhsani; Muhammad Arifin Badri (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the role of premarital counseling implemented by the KUA of Puring sub-district in reducing early marriage. Using a descriptive qualitative approach, this study examines the implementation of the "Go to School" program, which educates adolescents about the consequences and risks of early marriage. Primary data were collected through interviews with the head of the KUA of Puring sub-district, counselors, prospective brides, and junior and senior high school students who participated in premarital counseling. To complement the primary data, the researchers also collected secondary data from various literatures such as books, journals, and Internet sites, which were reinforced by direct observation at the research site. The results showed that the program was successful in reducing the number of early marriages from 14 cases in 2022 to 12 cases in 2023, and further reduced to 9 cases in 2024. In addition, the program also provides an understanding of the law, health, and other aspects related to early marriage. Collaboration with Puskesmas to provide reproductive health education is an important part of this program. The results suggest that effective premarital counseling not only helps reduce early marriage, but also builds a younger generation that is better prepared for married life.